2019
DOI: 10.1590/1980-265x-tce-cicad-16-9
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Harm and Benefits of Adolescents About the Use of Marijuana, Province of Conception, Chile

Abstract: Objective: to identify the perception of harm and benefits of marijuana associated with the use of marijuana in high school students aged between 15 and 17 years. Method: quantitative, transversal, descriptive and correlational design. The sample consisted of 268 students from public educational institutions between the ages of 15 and 17 years from five communes in the Chilean province of Concepción. The independent variables were biodemographic (sex, age and course), age of onset, use of marijuana in friends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Objective knowledge about medical cannabis was low, not only among experts (Reece, Holle & Mukherjee 2021;Szaflarski et al 2020) and students in health care (Caligiuri, Ulrich & Welter 2018;Moeller, McGuire & Melton 2020;Pierre, Matthews & Walsh 2020;Sokratous et al 2021), but also among the general public (Gates, Todd & Copeland 2017). Nevertheless, studies with experts (Arnfinsen & Kisa 2021;Kaplan et al 2020;Szaflarski et al 2020), students (Moeller & Woods 2015), medical cannabis users (Arora et al 2020;Henriquez & Hamilton 2019;Luque et al 2021;Magnan & Ladd 2019), as well as the general public (Gazibara et al 2017) reported positive perceptions and attitudes toward medical cannabis. In some studies, higher perceived benefits were associated with lower risk perceptions (Jacobs, Kane & Caballero 2022;Shorey Fennell et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Objective knowledge about medical cannabis was low, not only among experts (Reece, Holle & Mukherjee 2021;Szaflarski et al 2020) and students in health care (Caligiuri, Ulrich & Welter 2018;Moeller, McGuire & Melton 2020;Pierre, Matthews & Walsh 2020;Sokratous et al 2021), but also among the general public (Gates, Todd & Copeland 2017). Nevertheless, studies with experts (Arnfinsen & Kisa 2021;Kaplan et al 2020;Szaflarski et al 2020), students (Moeller & Woods 2015), medical cannabis users (Arora et al 2020;Henriquez & Hamilton 2019;Luque et al 2021;Magnan & Ladd 2019), as well as the general public (Gazibara et al 2017) reported positive perceptions and attitudes toward medical cannabis. In some studies, higher perceived benefits were associated with lower risk perceptions (Jacobs, Kane & Caballero 2022;Shorey Fennell et al 2022).…”
Section: Introductionmentioning
confidence: 99%